Using Webquest to Improve Fun Writing for the Ninth Graders at MTs Madrasatul Qur'an Tebuireng Jombang - Wihastyanang, Wardani Dwi (Journal of English Teaching and Learning Issues, 2018)
This study intended to describe how the process of teaching and learning using WebQuest can develop the ninth graders’ writing ability of report text. The subjects included the 15 ninth graders. The students were taught to be able to write report texts by using WebQuest after they visit the web addresses given in the two cycles of classroom action research. Their writing ability achievement and the information on students’ interaction during the teaching and learning process were attained by overseeing writing products at the end of each cycle and by using observation checklists and field notes. The result indicated that WebQuest was successful in developing the students’ writing ability of report texts. The comparison of the students’ scores in the preliminary study and in Cycle 2 was significantly developed. In preliminary study, the students’ average score was 50.8. While in the cycle two, the students’ score was 76.8.